FITNESS acts as a negative regulator of immunity and influences the plant reproductive output after Pseudomonas syringae infection - Mengarelli, Diego Alberto (2021)
Fil: Fil: Mengarelli, Diego Alberto. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.